2016
DOI: 10.1186/s12968-017-0332-z
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of myocardial injury after reperfused infarction by T1ρ cardiovascular magnetic resonance

Abstract: BackgroundThe evolution of T1ρ and of other endogenous contrast methods (T2, T1) in the first month after reperfused myocardial infarction (MI) is uncertain. We conducted a study of reperfused MI in pigs to serially monitor T1ρ, T2 and T1 relaxation, scar size and transmurality at 1 and 4 weeks post-MI.MethodsTen Yorkshire swine underwent 90 min of occlusion of the circumflex artery and reperfusion. T1ρ, T2 and native T1 maps and late gadolinium enhanced (LGE) cardiovascular magnetic resonance (CMR) data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Contijoch et al recently reported a retrospective self‐gated golden‐ratio CMR technique analogous to the presented ECG‐based approach. That study nicely demonstrated its use for cine imaging of subjects with premature ventricular contractions . In this study, feasibility and relative efficiency of beat‐type gating was demonstrated for more‐general imaging of sinus rhythm and atrial fibrillation as well as intermittent premature beats.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Contijoch et al recently reported a retrospective self‐gated golden‐ratio CMR technique analogous to the presented ECG‐based approach. That study nicely demonstrated its use for cine imaging of subjects with premature ventricular contractions . In this study, feasibility and relative efficiency of beat‐type gating was demonstrated for more‐general imaging of sinus rhythm and atrial fibrillation as well as intermittent premature beats.…”
Section: Discussionmentioning
confidence: 68%
“…That study nicely demonstrated its use for cine imaging of subjects with premature ventricular contractions. 27,28 In this study, feasibility and relative efficiency of beat-type gating was demonstrated for more-general F I G U R E 6 Beat-type gated imaging of pacing simulated premature beats. Paced premature beats were introduced every 5 beats.…”
Section: Comparison To Other Arrhythmia Imaging Techniquesmentioning
confidence: 97%
“…Noncontrast magnetic resonance imaging approaches based on the measurement of myocardial relaxation rates,34, 35 magnetization transfer,36 and apparent diffusivity21 have been reported; however, with the exception of T1 mapping–based techniques, these approaches remain experimental. In addition, traditional indexes of diffusion such as MD and FA may not show large variations in fully healed chronic infarcts 20, 37…”
Section: Discussionmentioning
confidence: 99%
“…LGE magnetic resonance imaging is commonly used for the detection of myocardial infarction [1][2][3][4] ; however, many patients with cardiovascular disease cannot receive gadolinium because of impaired renal function. 14 Noncontrast magnetic resonance imaging approaches based on the measurement of myocardial relaxation rates, 34,35 magnetization transfer, 36 and apparent diffusivity 21 have been reported; however, with the exception of T1 mapping-based techniques, these approaches remain experimental. In addition, traditional indexes of diffusion such as MD and FA may not show large variations in fully healed chronic infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…In the original version of this article [1], published on 15 February 2017, the author names were incorrectly displayed.…”
Section: Erratummentioning
confidence: 99%